UNRAVELING THE INTRICACIES OF TRANSLATION UNITS AND SHIFTS IN THE DYNAMICS OF MULTILINGUAL COMMUNICATION (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: This article delves into the intricate world of translation units and shifts, unveiling their profound impact on cross-linguistic communication. Drawing insights from renowned works in translation studies, the author navigates through the complexities of these concepts with clarity and depth. By addressing the challenges faced by translators and offering strategies for enhancement, this article serves as a valuable resource for academics and practitioners in the field. Readers are invited to explore the transformative power of translation units and shifts in fostering intercultural understanding and embracing linguistic diversity.